Study of the effects of peak/off-peak load shifting on hybrid power system storage using Power Pinch Analysis - Rozali, N.E.M. (Italian Association of Chemical Engineering - AIDIC, 2017)
The difference in electricity pricing based on the time of power use has led to load shifting from peak to off-peak hours in hybrid power systems (HPS). Apart from optimising electricity cost, shifting of load may also change the capacity of storage in the system. Power Pinch Analysis has been recently applied to guide load shifting aiming to minimise the cost of electricity, considering the peak and off-peak electricity pricing. This work extends the study by scrutinising the effects of peak/off-peak load shifting on the capacity of storage in HPS. Shifting heuristics are developed to ensure optimal storage size is achieved. Results show that the proposed load shifting strategy from peak to off-peak hours has successfully minimised the costs of both the storage system and the electricity bill. Copyright © 2017, AIDIC Servizi S.r.l.